GAMIFICATION TO IMPROVE STUDENTS’ ENGAGEMENT IN LEARNING ENGLISH - Hadirotun - Nikmah (Universitas Muhammadiyah Kalimantan Timur, 2020)
ABSTRACT This paper aim to review some theories and previous studies on the application of game-based learning platform to improve students’ engagement in learning English. Learning English is crucial and is not negotiable in an Industry 4.0 era to communicate and to collaborate globally. In fact, not a few students find it difficult and lack of enthusiasm in learning English. One of the major problems is the teaching method which is less interesting and tends to be boring. Therefore, one of the solutions to resolve this problem is through the implementation of gamification. One of the most well-known employed gamification tools is Kahoot. Kahoot is one of the most used application to impove students’ engagement in learning English. Kahoot is a free game-based learning platform that can be used by teachers and students. Hence, this paper will describe at first the challenges in teaching English language in digital era. Further, it discusses the theory of gamification in education, advantages of gamification, the description of Kahoot, advantages of using Kahoot and how to apply Kahoot in English classroom. Some previous research highlighting the effect of using Kahoot on the students’ engagement in learning English is the main point covered next. The last part of this paper will present conclusion and pedagogical implication as a closing note. Keywords : gamification, Kahoot, students’ engagement